Tingkat Konsumsi Kalsium, Seng, Vitamin E Dan Dismenorea Primer pada Siswi SMA - Putu Datisia Werdi Saraswati; I Putu Suiraoka; A.A. Ngurah Kusumajaya (Jurnal Kesehatan, 2020)
Total of 54,89% of childbearing age women in Indonesia experience primary dysmenorrhea. The intake of micronutrients such as Calcium, Zinc, Vitamin E can help in relieving the pain. This study aimed to find out the relationship between the level of calcium, zinc, and vitamin E consumption with the primary dysmenorrhea in female students at SMA Negeri 8 Denpasar. This study used observational research with a cross-sectional approach to support the research. 65 people were taken as samples using the simple random sampling technique. The chi-square was used as the statistical test in this study. The result of the study showed that most of the samples had low-level consumption of Calcium (87,7%), Zinc (78,5%), and vitamin E (95.4%), and 70,8% of the samples had primary dysmenorrhea. Based on the result, there was a relationship between the level of Calcium, Zinc, and Vitamin E consumption with primary dysmenorrhea. The better level of Calcium, Zinc, and Vitamin E consumption, the fewer women will experience dysmenorrhea. It is necessary to provide counseling that is related to alternative dysmenorrhea prevention, especially regarding the role of nutrients that can be used as dysmenorrhea therapy.